The conjunctural in international law: the revolutionary struggle against semi-peripheral sovereignty in Iraq - Hammoudi, Ali (Third World Quarterly, 2016)
This article will detail an event of revolutionary action in the historiography of anti-colonial and anti-imperial struggle in Iraq, namely al-Wathba (‘the leap’) of 1948, utilising it as an example to address the limitations of the methodology and analysis of Third World Approaches to International Law (TWAIL) scholarship. I will argue that there is a disconnect between notions of agency and structure in TWAIL analyses and that therefore TWAIL scholars should consider studying the conjunctures that allowed certain movements ample room to struggle against the imperialism of international law in the first place. I will use the example of the Wathba to illustrate how a conjunctural analysis may be undertaken, analysing its implications for the international legal order. I will then move to highlight the significance of labour to the conjuncture in question. Finally, I will demonstrate how events like the Wathba illuminate the transient and provisional nature of the foundations of international law, while emphasising its structural constraints.
Keywords: Ali Hammoudi